The role of Iraqi satellite channels in arranging students’ priorities regarding issues of political awareness(Survey study of a sample of students of the College of Political Science - University of Baghdad as a model) - MAJEED, M. MOHAMMED KADHIM (The journal of contemporary issues in business and government, 2020)
This research is descriptive research in its kind, and it uses the survey method in the context of what is related to allowing the target audience in the research in order to identify the students' opinions about the role of satellite channels in relation to issues of political awareness. The research aims to reveal the most prominent issues of political awareness that the Iraqi satellite channels contributed to in arranging priorities for students, and to identify the most prominent satellite channels that contributed to the order of priorities, as well as an explanation of the job roles played by these channels regarding issues of political awareness. The research required dividing it into three sections. The first topic dealt with the methodological framework of the research, which included the research problem, its importance, objectives and methodology, as well as the research community, its sample and fields. Practical research, which included the presentation and interpretation of the results of the analysis.